It can be done in government : an approach for improving efficiency in the public sector - Ford, Stanford E.; Martel, Deborah A.; Wright, Dianne A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"In this work titled, It Can Be Done: An Approach for Improving Efficiency in the Public Sector, we attempt to provide a roadmap describing a simple approach for improving processes using teams. This book is ideal for process improvement initiatives, academic institutions, organizational change practitioners, public entities, and administrators and leaders seeking a practical approach for the promotion and implementation of organizational effectiveness. Throughout this handbook, the term process refers to a series of steps that create a product or service. Processes are different from projects. Projects have a beginning and an end. Processes are ongoing, cyclical, and rarely operate in isolation. They connect to or impact many other processes. An approach to improve these processes is the focus of this book. As a public sector leader, you are encouraged, more often than not, to have an external perspective looking outside, looking long term. You are told to keep your eyes on the horizon, spend time figuring out what the public or the customer wants, to pay attention to what other similar organizations are doing, build external partnerships, network, and analyze both the external opportunities and threats. The truth is, however, the leaders and organizations that stand out are those who, contrary to this traditional approach, aggressively look internally, with a balance, more likely, of 80% internal and 20% external, particularly within the public sector"--